Review on immunity in viral infections - GEORGE, RINKI SUSAN; MURALIDHARAN.N.P.,; ANITHA ROY., (The journal of contemporary issues in business and government, 2020)
Novel interactions and effective modelling of the immune function is necessary for the development of antiviral mechanisms against the infectious viral disease . The immune system is intrinsic to health and is variable in humans due to the heritable and non-heritable influences. The key to identifying the risk of immune mediated and infectious diseases must be to understand and know the human immune system. The main components that develop immune responses include natural killer cells, cytokines, vaccines, Helper T cells. The cytokine and the chemokines play a crucial role in the induction of the antiviral mechanisms thereby deteriorating the level of viral replication. The natural killer cells are effector cells of the innate immune systems. The helper T cells play a pivotal role in inducing cell mediated immunity. The plasmid DNA vaccines induce strong and long lasting humoral (antibodies) and cell mediated (T- helper cell , other cytokine function cells and cytotoxic T cells), immune response without creating a risk of infection to the host's immune system. The cell mediated immunity is a type of immune response that involves the activation of the phagocytes, cytotoxic T-lymphocytes and various cytokines in response to the antigen without the production of antibodies. The mucosal immune system is an adaptive immune system associated with mucosal sites such as the gut mucosa that comprises Peyer's patches, cryptopatches, isolated lymphoid follicles in the gut antimesenteric wall, and the mesenteric lymph nodes. The aim of the review is to highlight the various antiviral defense mechanisms to boost the immunity.